Industrial building system : does it good for sustainable building? / S. Roshanfekr, N. M Tawil and N. A. Goh - Roshanfekr, S.; Tawil, N. M; Goh, N. A. (2015)
Housing and building construction is an important principle in sustainable development. The industrialization of building systems has been found to be necessary due to several factors: the fast and continuing progress of today’s world, the industrialization of many aspects of modern living, significant population growth, and the inadequacy and incompetence of conventional construction methods particularly in dense housing situations. This paper investigates the relevance of these factors as the drivers for changing people’s habits and perspectives toward building construction and to justify the introduction of industrialized construction approaches to replace the outdated conventional methods as well as the necessity to provide training in order to achieve product quality.